The performance, wear characteristics, and failures of austenitic manganese-steel castings used in crushing and rod milling - D. D. Howat; D. P. Enright (The Southern African Institute of Mining and Metallurgy, 1980)
Austenitic manganese-steel castings are very widely used in crushing and grinding in the' gold-mining industry in South Africa, The service life of a casting in a short-head crusher is difficult to predict because there are no clear-cut criteria by which such a judgement can be made, The addition of molybdenum and zirconium to the castings for crushers failed to result in improved performance, The results of extensive tests with through-hardened steel castings were very disappointing, mainly because of a design factor in the bowl liner. The design of the bowl liner is an important determinant of the life and performance of these castings. The extent to which the material in a crusher is reduced in size has profound effects on the consumption of metal and power, and on the effective life of a casting. Tests on manganese-steel castings in an 8 ft by 12 ft rod mill provided data on the total consumption of metal, and on the variations in the pattern and rates of wear of liners over lengthy periods. Progressive changes in the wear profiles of the lifter bars and the other liner components showed unexpected features. There are clear indications that, whereas a set of lifter bars will at first lift the charge strongly with relatively little slippage, there is a later period characterized by more slippage and greater wear on all the liner components.